Suspending non-substantive judicial decisions: An under-applied clause in the criminal procedure (Academic Journal of Internal Affairs, 2015)
The author provides an overview of the human rights implications of not suspending coercive measures until criminal trials become final and binding in Hungary.
Keywords: coercive measures; suspension of enforcement; Hungary